FORGIVENESS AND HAPPINESS THROUGH RESILIENCE - Sudirman, Subhan Ajrin; Suud, Fitriah M; Rouzi, Kana Safrina; Sari, Dewi Purnama (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The aim of this study was to examine the correlation between forgiveness and happiness among college students, with a particular focus on the role of resilience in mediating the forgiveness-happiness correlation. Participants consisted of 203 undergraduate students enrolled at a private university in center of Java who completed the subjective happiness scale, Heartland forgiveness scale, and Connor-Davidson Resilience scale. Result of mediational analysis cinfirmed the hypothesis, revealing the resilience partially mediated the correlation between forgiveness and happiness with the overall model explaining 27 percent of the variance in happiness.?